Plasma Electromagnetic Diagnostics On Tokamak Systems - A.S. Alhasi; A. Mohamed (Scientific Journal of University of Benghazi, 2026)
In this work, we try to bridge the gaps between electromagnetic theory and the experimental work. In this study, the magnetic field ( B),the plasma current (I), the Ohmic power (P) and finally the plasma electron temperature (Te) are covered. To simplify the approach, we adhere to plasmas, with circular cross-section. Thus we use the geometry of the torus, where (φ) is in the toroidal direction and () is in the poloidal direction